ChemInform Abstract: Palladium‐Catalyzed Cyanoalkenylation of Indoles. Issue 45 (14th October 2013) - Kianmehr, Ebrahim; Hashemi, Hamed; Darvish, Ali
Abstract An efficient method for the Pd‐catalyzed cyanoalkylation of 3‐iodoindoles is developed using internal alkynes with K4Fe(CN)6 as the cyanide source.